2020
DOI: 10.20853/34-3-3466
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the "new normal": University leaders and marketisation

Abstract: This article explores how leaders, key decision-makers in research-intensive public universities perceive marketisation in the sector in relation to public-private arrangements in teaching and learning provision. The focus is on the nature of relationships between public universities and those private companies engaged in the co-creation, delivery and support of educational provision. It draws on 16 interviews with decision makers-senior leaders and managers in higher education at six research-intensive univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…However, academics and students have demonstrated exceptional resilience, and are finding creative solutions to meeting the teaching and learning needs (Czerniewicz 2020). It is further argued that, even though there are different views and perspectives on the importance and complex nature of relationships between private companies and public universities in general, student learning is explicitly prioritised, even in the midst of deep disruptions such as those caused by Covid-19 (Czerniewicz et al 2020).…”
Section: Priority Conflictmentioning
confidence: 99%
“…However, academics and students have demonstrated exceptional resilience, and are finding creative solutions to meeting the teaching and learning needs (Czerniewicz 2020). It is further argued that, even though there are different views and perspectives on the importance and complex nature of relationships between private companies and public universities in general, student learning is explicitly prioritised, even in the midst of deep disruptions such as those caused by Covid-19 (Czerniewicz et al 2020).…”
Section: Priority Conflictmentioning
confidence: 99%
“…One study found that teaching academics do not support the involvement of external for-profit providers in teaching and learning provision (Jaschik and Lederman 2019) while another found the experience negative for academics employed on precarious conditions (Kaktiņš 2018). Elsewhere in our overarching study, we analysed senior leaders' sense making of these relationships and found them to be ambivalent (Czerniewicz et al 2020;Swartz et al 2018).…”
Section: Marketisationmentioning
confidence: 99%